Cardiac Microvascular Rarefaction in Hyperthyroidism‐Induced Left Ventricle Dysfunction. (12th October 2013) - Freitas, Felipe; Estato, Vanessa; Carvalho, Vinícius Frias; Torres, Rafael Carvalho; Lessa, Marcos Adriano; Tibiriçá, Eduardo
Abstract Objective The pathophysiology underlying hyperthyroidism‐induced left ventricle (LV) dysfunction and hypertrophy directly involves the heart and indirectly involves the neuroendocrine systems. The effects of hyperthyroidism on the microcirculation are still controversial in experimental models. We investigated the effects of hyperthyroidism on the cardiac function and microcirculation of an experimental rat model. Methods Male Wistar rats (170–250 g) were divided into two groups: the euthyroid group (n = 10), which was treated with 0.9% saline solution, and the hyperthyroid group (n = 10), which was treated with l‐thyroxine (600 μg/kg/day, i.p.) during 14 days. An echocardiographic study was performed to evaluate the alterations in cardiac function, structure and geometry. The structural capillary density and the expression of angiotensin II AT1 receptor in the LV were analyzed using histochemistry and immunohistochemistry, respectively. Results Hyperthyroidism was found to induce profound cardiovascular alterations, such as systolic hypertension, tachycardia, LV dysfunction, cardiac hypertrophy, and myocardial fibrosis. This study demonstrates the existence of structural capillary rarefaction and the down‐regulation of the cardiac angiotensin II AT1 receptor in the myocardium of hyperthyroid rats in comparison with euthyroid rats. Conclusions Microvascular rarefaction may be involved in the pathophysiology of hyperthyroidism‐induced cardiovascular alterations.